2019
DOI: 10.3390/polym11010115
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Oxidase Immobilized on a Functional Polymer Modified Glassy Carbon Electrode and Its Molecule Recognition of Glucose

Abstract: In the present study, a glucose oxidase (GluOx) direct electron transfer was realized on an aminated polyethylene glycol (mPEG), carboxylic acid functionalized multi-walled carbon nanotubes (fMWCNTs), and ionic liquid (IL) composite functional polymer modified glassy carbon electrode (GCE). The amino groups in PEG, carboxyl groups in multi-walled carbon nanotubes, and IL may have a better synergistic effect, thus more effectively adjust the hydrophobicity, stability, conductivity, and biocompatibility of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…The effects of MWCNTs, HFs, and BSA on the catalytic activity of GOD were studied using an ultraviolet and visible spectrophotometer (UV-vis spectrophotometer) (Evolution 220, Thermo, Shanghai, China) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The effects of MWCNTs, HFs, and BSA on the catalytic activity of GOD were studied using an ultraviolet and visible spectrophotometer (UV-vis spectrophotometer) (Evolution 220, Thermo, Shanghai, China) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…TEM (JEM-2100, JEOL, Tokyo, Japan) images of MWCNTs, MWCNTs-CTAB, HFs, and HFs-Lac were taken at 200 KV [ 48 ]. The spectroscopic study of laccase catalyzing rutin was carried out on an ultraviolet and visible spectrophotometer (UV-vis spectrophotometer) (Evolution 220, Thermo, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…One of the most frequently used electrochemical methods is voltammetry with modified GCEs (unmodified electrodes are not preferred as they are characterized by a smaller range of linearity, lower limits of detection, and quantitation and a large overpotential). Numerous studies have shown that modification of electrodes with poly-L-amino, acid coatings, and/or coatings containing carbon nanoparticles improve their performance [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…L-amino acid duplicated biosensors have also found application in the detection of drugs with a pyrazine motif. Research has been performed using differential impulse voltammetry on a sensor containing poly-L-methionine and electrochemically reduced graphene oxide/GCE to detect PZA in urine, plasma, and pharmaceuticals [24]. Similar stud- L-amino acid duplicated biosensors have also found application in the detection of drugs with a pyrazine motif.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation